The Rise of Female Ulama in Indonesia: A Gender Perspective - Yanuardi Syukur (Review of Islam in Southeast Asia, 2018)
This article tries to see the contestation and affirmation of female ulama (muslim scholars) in contemporary Indonesia.The common patriarchal system in Indonesia has made the role of female clergy not so visible which is very different from the role of ulama which is generally attributed to men.With a gender perspective, this paper tries to see the affirmation process of femaleulama in Indonesia conducted by muslim women organizations and NGOs in the discourse on the roles of men and women.Among interesting discourse was raised by the Indonesian Women Ulema Congress (KUPI) conducted in April 2017 in Cirebon, West Java. Women activists and ulema discussed strategic issues on Islamic studies, women movement, economic empowerment and national politics of how women have to get more access and to take a stronger leadership role in national and regional level.